Reconceptualising Distance Learning as the Foundation of Educational Resilience - Kurniawan Maspul; Muhammad Taha (Frontiers in Research Journal, 2025)
The shuttered schoolhouse has become a devastating symbol of our disrupted world, where pandemics, climate disasters, and conflict systematically dismantle educational continuity for millions. Moving beyond the pandemic’s emergency remote teaching, this paper reconceptualises distance learning not as a provisional substitute but as a critical 'resilience infrastructure' for a perilous century. With climate change alone disrupting schooling for over 43 million children in 2022 (UNICEF, 2023) and the digital divide excluding nearly a third of students during the COVID-19 peak (UNICEF, 2020), the fragility of place-based education is a strategic and moral failure. This study argues that the central challenge is not technological but political and pedagogical: to engineer distance learning as an equitable public good. Synthesising global evidence from UNESCO, OECD, and scholarly research, analysing the design levers—from fostering Community of Inquiry to applying equity-first cognitive principles—that can transform digital spaces from sites of isolation into engines of belonging and rigorous learning. The findings present an urgent call to action: by investing in robust, accessible distance learning systems, we can safeguard educational justice, protect against future shocks, and honour the fundamental right to learning for every child, regardless of circumstance.